Concept of passive devices based on low-contrast periodic structures - Konoplev, I; MacLachlan, A; Robertson, C; Cross, A; Phelps, A (2011)
The surface periodic structures with and without localized defects and operating in the mm and submm wavelength range can be used to control the fluxes of electromagnetic radiation via formation of reconfigurable pass and stop bands as well as exhibiting novel dispersive characteristics. Such structures can be used to form high-Q cavities, narrow band reflectors, tunable filters and pulse-forming lines. The structures can be observed either via machining of small one-/two-dimensional perturbations on waveguide's walls or by lining the wall with a dielectric which has a periodic refractive index. The structures observed via machining of the waveguide walls are compatible with different active media including high-current electron beams and plasmas while the structures based on dielectric can be used to observe adaptable and tunable components. Taking into account that surface lattices can be easily cooled the devices based on such structures are compatible for high power environments in contrast with conventional metamaterials. In this work we discuss one-dimensional (1D) and twodimensional (2D) lattices and their possible use in a number of diverse applications: from particle acceleration to materials research. The results of the recent theoretical and experimental studies will be presented.